Should we always trust hypographeis? When palaeography contradicts the text: the case of P.Cair.Masp. III 67296 - Briasco, Livia (Scrineum, 2024)
This paper focuses on a contract preserved in the Dioskoros archive, whose two issuers are explicitly presented as illiterates by a certain Flavius Theoteknos son of Psais, subscribing on their behalf. The analysis not only of the handwriting but also of the use of graphic symbols completes the profile of this individual, already known by scholars for his network on one side and poor Greek skills on the other. Moreover, the detection of another hand involved in the subscriptions section of P.Cair.Masp. III 67296 opens up an unusual scenery, reiterating the key importance of in-depth palaeographical analysis in the study of literacy.